Assessment of Automobile Engines Rebuilt at Local Artisan Workshops in Ghana - Prince Yaw Andoh; Godwin Kafui Ayetor; Godwin Kafui Ayetor; Kofi Owura Amoabeng; Michael Nii Sackey Sackey (Journal of Applied Engineering and Technological Science (JAETS), 2022)
The manufacturing industry of Ghana, as promising as it is, has many shaping to be done. This specifically goes to the automobile manufacturers and engine rebuilders of Ghana. Though agile and very skillful in rebuilding engines many have reported grievances on their service renders to them. This shows that, the knowledge and zeal to rebuild it puts the industry at a certain level but needs further additional and requisite tuning to reach the pinnacle. For this reason, the researcher therefore sought to investigate how cylinder bores and piston ring end-gap contribute to the failure of locally rebuilt engines. A descriptive design was used for the study and sample of 60 participants responded to the structured questionnaire. The study used primary data to provide reliable and up-to-date information the researcher needs for the analysis. The data were entered in SPSS with analysis performed using inferential and descriptive analysis methods. The findings of the study revealed that errors made in the work procedure had a stronger effect on the clients’ than its other counterpart. Practically, the flaws in the work procedure of rebuilding cylinder bore significantly affects clients’ satisfaction.